ChemInform Abstract: A New Method for C—H Functionalization of Aliphatic Compounds by an Unusual Photochemical Reaction of Diazoketones Without Elimination of Nitrogen. Issue 39 (September 2016) - Rodina, Liudmila L.; Galkina, Olesia S.; Maas, Gerhard; Platz, Matthew S.; Nikolaev, Valerij A.
Abstract: Benzophenone‐sensitized reactions of diazotetrahydrofuranones with H‐donors like tetrahydrofuran, dioxane, cyclohexane, and diethyl ether, occur without elimination of nitrogen and give rise to the formation of N‐substituted hydrazones or bis‐hydrazonoethanes, due to a formal insertion of the terminal N‐atom of the diazo group into α‐C‐H bonds of ethers and aliphatic hydrocarbons.